Electrospun Nanofibrous Materials for Biomedical Textiles. (2020) - Sinha, M.K.; Das, B.R.; Bharathi, D.; Prasad, N.E.; Kishore, B.; Raj, P.; Kumar, K.
Abstract: A comprehensive paper is presented with the actual practical application of nanomaterial as a nanofiber and reported with useful research data for biomedical textiles applications. The present paper is aimed at DMSRDE current nanofiber research and its significant findings, emphasizing more on functional protective capabilities and challenges. Additionally, this paper elucidates current research to introduce bioprotective applications using nanowebs. This research has revealed that NS technology is promising for development of lighter weight functional fabrics with enhanced comfort, particularly for military clothing equipment. The emphasis of integration of nanowebs with Defense protective textiles (DPTs) is broadly targeted at the introduction of biological protection and enhancement of usable life of clothing structure. The nanowebs of polyvinyl alcohol (PVA) and Chitosan are exploited for the development of biological protection in DPTs and other nanowebs like polyvinylidene difluoride (PVDF) and Polystyrene-butadiene rubber (PSBR) webs are for enhancement of functional features in DPTs. The most important achievement with such research is the establishment of a technology for bulk productionization of functional fabrics